The Influence of Motivation, Work Environment, and Leadership on Employee Work Productivity at PT. Pos Indonesia Persero - Sherly Novianti; Suparmono Suparmono (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2021)
Abstract This study aims to analyze the effect of motivation, work for the environment, and leadership on employee productivity partially. This research was conducted at PT Pos Indonesia Plemburan Yogyakarta branch. The population in this study were permanent employees of PT Pos Indonesia Plemburan Yogyakarta branch, amounting to 114 employees with non-probability sampling technique using a purposive sampling method. This type of research used a survey method and used a quantitative approach. Based on the results of the study using the t-test, it was found that the motivation variable had a significant effect on employee work productivity. The result is that motivation, work environment, and leadership have a positive and significant effect on the work productivity of employees at PT Pos Indonesia Plemburan Yogyakarta Branch. Meanwhile, based on the results of the coefficient of determination test (R2) of 0.302 or 30.2%.